Is There a Place for Pantheism in (Post-)Christian Ecofeminist Reconstruction of the God/Goddess–World Relationship - Furlan-Štante, Nadja (Religions, 2024)
This paper is an attempt to consider an alternative pluralist pantheism (Mary Jane Rubenstein) as the next step in the evolution of interpersonal, interspecies, and God–human–nature relationships and its possible realisation in (post-)Christian ecofeminism and its epistemology. It follows the methodology and epistemology of theological ecofeminism, which assumes that the oppression of women and the exploitation of nature stem from the same constellation of phenomena: patriarchal domination, dualistic anthropologies, and global hypercapitalism. Recognising that pantheism is a very complex phenomenon and should not be viewed as a single codified viewpoint, but rather as a diverse family of different doctrines, this paper understands pantheism primarily as the paradigm that asserts that everything is part of a divine unity consisting of an all-encompassing, manifested deity or God/Goddess. The paper first explains the pan-en-theistic turn in Christian ecofeminism as a tool for deconstructing the dominant Cartesian dualistic binaries and their symbolism and metanarratives, and as the first “safe” phase of transition from Christian anthropocentrism. From this standpoint, Grace M. Jantzen’s defense of pantheism as an alternative to transcendental theism is further explored as she argues that divinity is found “in” the physical and material world and nowhere else. The paper then moves to the second phase, proposed in the final part of the paper, on the possibility of the theoretical adoption of pluralist pantheism in (post-)Christian ecofeminist ecotheology. Here, the question of the “fear and horror of pantheism” in Western thought is discussed.